Structural and Dielectrical Properties of Ag- and Ba-Substituted Hydroxyapatites - Kaygili, Omer; Keser, Serhat; Dorozhkin, Sergey V.; Yakuphanoğlu, Fahrettin; Al-Ghamdi, Ahmed A.; Kirbag, Sevda; Gursoy, N. Canan (Springer, 2014)
Ag- and Ba-doped hydroxyapatite (HAp) samples were synthesized by sol-gel method. The crystallite sizes for all the samples were found to vary from 26 to 39 nm. Neither Ag nor Ba did result in dramatic changes in the morphology of all the samples, and the Ca/P molar ratio was varied. The dielectric parameters of the samples were changed with the dopant content. The maximum and minimum values of the dielectric constant were observed for 2.0 %Ba-HAp and 0.5 %Ba-HAp samples. The alternating current conductivity indicates that all the samples exhibit the insulator behavior. The results of the biological tests revealed that Ag-containing samples have an antimicrobial activity, while no antimicrobial activity was detected for both HAp and Ba-doped HAp samples.
Keywords: Dielectric property; Antimicrobial activity; Hydroxyapatite; Crystallinity